Frequency Domain Structural Synthesis Applied to Quasi-Static Crack Growth Modeling - Young W. Kwon; Joshua H. Gordis (Shock and Vibration)
Quasi-static crack growth in a composite beam was modeled using the structural synthesis technique along with a finite element model. The considered crack was an interface crack in the shear mode (i.e. mode II), which occurs frequently in the scarf joint of composite structures. The analysis model was a composite beam with an edge crack at the midplane of the beam subjected to a three-point bending load. In the finite element model, beam finite elements with translational degrees of freedom only were used to model the crack conveniently. Then, frequency domain structural synthesis (substructure coupling) was applied to reduce the computational time associated with a repeated finite element calculation with crack growth. The quasi-static interface crack growth in a composite beam was predicted using the developed computational technique, and its result was compared to experimental data. The computational and experimental results agree well. In addition, the substructure-based synthesis technique showed the significantly improved computational efficiency when compared to the conventional full analysis.